The halberd at Red Cliff Jian'an and the Three Kingdoms - Tian, Xiaofei 1971- (Harvard-Yenching Institute monograph series, 2018)
"The writings of the Jian'an era lay the foundation of China's classical poetry and literary criticism and its personages and events have inspired works of historical fiction and drama throughout Chinese history. This book investigates how these associations were closely related in their origins and subsequent metamorphoses"--Provided by publisher.